Síntese, modificação e caracterização de resinas poliméricas e sua avaliação na remoção de amônia da água - Deus, Laylana Cornélio de. (2018)
This work developed the modification and characterization of a new porous crosslinked polymer resin (poly (glycidyl methacrylate-co-divinylbenzene)) in order to evaluate its efficiency of removal of ammonia from water by adsorption comparing it with resins already known and used as : poly (styrene-co-divinylbenzene) (STY-DVB) and divivilbenzene (DVB). The objective of this dissertation is to sulfonate the GMADVB resin so that it is efficient in the adsorption of ammonia in the water in order to be a cheaper alternative (when compared to STY-DVB and DVB) for the polishing of aqueous solutions containing low concentrations of ammonia, for the technical specification Feema, NT 202, R-10, 1986. The three previously synthesized polymer resins were modified via the sulfonation reaction using variable reaction times. The resins that showed integrity after the sulphonation process and greater exchange capacity were: STY-DVB1 (exchange capacity Q = 3.35 mmol / g), DVBS2 (exchange capacity Q = 2.70 mmol / g) and GMA -DVBS2 (exchange capacity Q = 2.75 mmol / g). Such resins were characterized, which proved their chemical modification, and properties as porosity. Then, their capacity to adsorb ammonia in the batch regime in relation to the mass variation (0.05g, 0.1g, 0.3g, 0.7g and 1g) and the influence on the time variation (5min, 10min, 15min, 30min and 60min). It was concluded after the tests that the GMA-DVBS2 resin is efficient in the adsorption of ammonia from the water, for the proposed purposes, possessing characteristic isotherms of an adsorptive material with macropores.